Web-Based Tuition Payment Information System Design Using Codeigniter at SMA Negeri 2 Bungku - Wulansari, Lusiana; Iskandar, Akbar; Syahrul, Syahrul; Mansyur, Mansyur; Ramazanova, Makhabbat; Saputri S, Dian (Ceddi Journal of Education, 2025)
The advancement of digital technology has transformed administrative processes in the education sector, driving the need for modern and efficient solutions. At SMA Negeri 2 Bungku, tuition payment (SPP) management was previously conducted manually, posing risks such as data inaccuracy, loss, and delays in reporting. This study introduces an innovative web-based tuition payment information system developed using the CodeIgniter framework and the Waterfall development model, encompassing stages of requirements analysis, system design, implementation, and testing. The proposed system offers a significant shift from manual to automated financial administration, enabling real-time data recording, transparent transaction histories, and automated report generation. A key innovation lies in the integration of features such as digital receipts, printable transaction summaries, and centralized student data management, all accessible through a user-friendly web interface. Evaluation results show a marked improvement in administrative efficiency, user satisfaction, and data accuracy. This system not only streamlines school financial operations but also sets a practical example for other educational institutions seeking to digitize their administrative services. The research contributes to the development of scalable and adaptable digital solutions in the education sector, enhancing transparency, accountability, and service quality.